Unraveling Students’ Strategies in Overcoming the Listening Comprehension Problems - Agung Suhadi; Kiagus Baluqiah; Hanniffa Putri Pertiwi (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Understanding the listening comprehension strategy plays important role for students successfull to upgrade their listening test and TOEFL score as well. This aims to investigate deeply the students’ strategies in overcoming listening comprehension problems. The descriptive qualitative method is applied toward the third semester students of English Education study program Muhammadiyah University of Bengkulu. This research took 51 students who have taken listening courseworks (listening 1 and 3). Data collection technique were conducted by giving questionnaires in the light of Rebbica’s theory (1993); direct and indirect strategies. The results of study showed there were some problems faced by the third semester students in conducting listening comprehension test, such as unfimiliar words, complex grammatical structure, lack of concentration, pronunciation, obscure form of speech, long answer question, and accents. Whilst, most of students used cognitive strategy in overcoming their problem in listening comprehension. To sump up, students must to learn some listening strategies as an effort to anticipate their problems when conduct listening comprehension test.